Phytochemical analysis and screening of the fungus Calostoma Sp. found in Tawau for bioactive and pharmacologically active compounds - Noramly Muslim; Maryati Mohamed; Mohd. Aliff Iskandar (Universiti Malaysia Sabah, 2009)
The purpose of this research is to analyze the potential of the polysaccharides extracted from Calostoma sp. mushroom, which is proven to have bioactive properties through bioassays. The morphology of the genus Calostoma was investigated by scanning electron microscope and light microscopy showed differences. The mushroom species was confirmed as Calostoma insignis. The antimicrobial tests of crude polysaccharide extracts of C. insignis on three bacterial pathogens were done by disk diffusion and agar overlay techniques. The sensitivity of test pathogens was in decreasing order: P. aeruginosa > S. aureus > E. coli. The antioxidant assays shows promising results in Ascorbic acid Equivalent Antioxidant Capacity assay (ICso = 184 µg/mL). The Trolox Equivalent Antioxidant Capacity assay showed values of 1 mg/mL and 2 mg/mL and the Ferric Reducing Ability of Plasma assay showed values of 87 mrnol/g and 297 mrnol/g for ethanolic and aqueous extracts respectively. The aqueous extract had a higher potency antioxidant activity than ethanolic extract. The ethanolic extract inhibited the growth of some bacteria proves that C. insignis may be tantamount to treat strains of bacteria. These findings are of significance to use the fruit-bodies for antioxidant and antimicrobial activities to reduce the demands on endangered species.